2014
DOI: 10.5031/v5i1.ria10245
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da frequência ventilatória sobre os índices da variabilidade da frequência cardíaca

Abstract: Introdução e objetivos: O objetivo deste estudo foi mensurar os efeitos do ritmo ventilatório na regulação do tônus simpático, avaliada a partir de variáveis referentes à variabilidade da frequência cardíaca (VFC). Métodos: Foram envolvidos no estudo 15 voluntários fisicamente ativos, estudantes de Educação Física, os quais realizaram três intervenções, organizadas de maneira aleatória, com frequência ventilatória (FV) a 6, 15 e 24 ciclos por minuto (cpm). Registraram-se as medidas de VFC e da frequência cardí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
1
1
0
2
Order By: Relevance
“…According to our findings, studies comparing controlled and spontaneous breathing rhythm conditions reported significant changes in all HRV domains (Barth & Vecchio, ; Tavareset al, ). These findings suggest that if breathing rate control is adopted during a baseline rest record, the values obtained will already be influenced by a variable that may change the HRV values, compromising the investigation of other variables that would have the potential to change the HRV indices.…”
Section: Discussionsupporting
confidence: 78%
“…According to our findings, studies comparing controlled and spontaneous breathing rhythm conditions reported significant changes in all HRV domains (Barth & Vecchio, ; Tavareset al, ). These findings suggest that if breathing rate control is adopted during a baseline rest record, the values obtained will already be influenced by a variable that may change the HRV values, compromising the investigation of other variables that would have the potential to change the HRV indices.…”
Section: Discussionsupporting
confidence: 78%
“…Quanto aos índices relacionados à VFC, sejam estes no domínio do tempo ou no domínio da frequência, os altos valores apresentados indicam haver funcionamento adequado dos mecanismos autonômicos. Sendo a VFC marcador do balanço autonômico, a correlação entre a VFC e os valores da FC está baseada no fato da FC aumentar em função da maior ativação do ramo simpático e reduzir seus valores frente ao aumento da atividade parassimpática (AUBERT; SEPS; BECKER, 2003;BARTH;. A partir da VFC e da variação de desempenho em testes motores, Oliveira et al (2012) identificaram que atletas de futebol que apresentaram maior ativação vagal foram mais responsivos ao treinamento, porém, os autores indicam que os mecanismos de aumento do desempenho relacionado ao aumento da ativação vagal ainda são desconhecidos.…”
Section: Discussionunclassified
“…Subjective Perceived Exertion: SPE was measured using the Borg Scale 23 after each training session. Heart rate variability: A cardiac monitor (Polar RS800CX; Kempele, Finland) 24 was used to record HRV. The data were recorded at the following time points: pre-warm-up, soon afterwards and 24h after each training session held.…”
Section: Data Collection and Recording Proceduresmentioning
confidence: 99%